Problematics of Individual Company as Legal Entity in Terms of Indonesian Omnibus Law on Job Creation Law - Pratama, Andistya; Hapsari, Dwi Ratna Indri; Harahap, Rahmi Fuji Astuti (Universitas Muhammadiyah Yogyakarta, 2025)
The introduction of Individual Companies, which can be established by a single individual, aims to streamline company management and legal recognition while enhancing Indonesia's investment climate. This study seeks to address two critical questions: How is the concept of an individual legal entity regulated under the Job Creation Law? And what is the legal position of the General Meeting of Shareholders (GMS) in a sole proprietorship that constitutes an individual legal entity? Employing a normative or doctrinal legal research approach with a regulatory focus, this study revealed that the concept of an Individual Company aligned with institutional theory. Both agreement and institutional theories were applied in managing such companies. The study further highlighted that GMS decisions in an Individual Company were executed as shareholder resolutions, which carried the same legal weight as GMS decisions in traditional companies, while the role of commissioners was effectively eliminated.